2016
DOI: 10.19071/jhcbt.2016.v2.2996
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability among Fusarium oxysporum isolates from melon (Cucumis melo) in Qazvin province, Iran

Abstract: <p><em>Fusarium</em> wilt, caused by <em>Fusarium oxysporum</em> f. sp. <em>melonis</em> (Fom), the soil-borne fungus that can due to more losses in yield of melon plants. Fusarium is a variable fungi in terms of morphology, symptom production, pathogenicity and wide host range. From 2013 to 2015, 120 isolates of <em>F. oxysporum,</em> <em>F. acuminatum, F. graminearum, </em> <em>F. proliferatum</em> and <em>F. solani</em>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The disease severity (30%) and disease intensity (25%) was recorded for KP 4 HM-15 while Punjab Sunehri was severely affected by the disease (100%) (Plate 1). The disease severity symptoms matched as described by Mahdikhani (2016). The MH-41 F 1 hybrid exhibited disease reaction similar to the female parent, KP 4 HM-15.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…The disease severity (30%) and disease intensity (25%) was recorded for KP 4 HM-15 while Punjab Sunehri was severely affected by the disease (100%) (Plate 1). The disease severity symptoms matched as described by Mahdikhani (2016). The MH-41 F 1 hybrid exhibited disease reaction similar to the female parent, KP 4 HM-15.…”
Section: Resultssupporting
confidence: 70%
“…Fusarium wilt incidence: The general symptoms on Fusarium infection include wilting, necrosis, gum exudates, stunting and discoloration as observed in melon male parent under field conditions (Punja et al, 2001). Mahdikhani (2016) also reported that Fusarium wilt affected melons exhibit prominent symptoms of wilting, yellowing and chlorosis of the foliage, less or no fruit bearing in partially affected vines, and finally decay of roots and death under severe infection conditions. The resistance to Fusarium wilt disease in the male and female parents of the hybrid is low and high, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation